1981
DOI: 10.1021/jo00338a028
|View full text |Cite
|
Sign up to set email alerts
|

Reactions of copper(I) halide complexes of trivalent phosphorus with vinylic halides

Abstract: The direct formation of the vinylic carbon to phosphorus bond has been accomplished via reaction of vinylic halides with copper® halide complexes of trialkyl phosphites. In addition, formation of varying amounts of vinylic chlorides may be observed if the reaction is performed by using vinylic bromides with copper® chloride complexes of trialkyl phosphites. This halogen-exchange reaction may be made synthetically useful through the employment of copper® chloride complexes of triaryl phosphites or phosphines.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

1982
1982
2018
2018

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(10 citation statements)
references
References 2 publications
(2 reference statements)
0
10
0
Order By: Relevance
“…Since the pioneering early work by Kosolapoff and McCullough in 1951, various synthetic methods for vinylphosphonate motifs have been developed over the past decades. The direct C–P bond forming approaches toward the synthesis of vinylphosphonates include transition-metal-catalyzed cross-coupling reactions of alkylphosphites with vinyl halides (Scheme , a), metal-promoted hydrophosphorylation reactions of terminal alkynes with dialkylphosphites (Scheme , b), and silver-mediated radical phosphonation reaction (Scheme , c) . Metalation of alkynylphosphonates via zirconation or titanation, yielding metallacycle intermediates, followed by hydrolysis of the intermediate, is an efficient route for the stereoselective synthesis of vinylphosphonates (Scheme , d).…”
Section: Introductionmentioning
confidence: 99%
“…Since the pioneering early work by Kosolapoff and McCullough in 1951, various synthetic methods for vinylphosphonate motifs have been developed over the past decades. The direct C–P bond forming approaches toward the synthesis of vinylphosphonates include transition-metal-catalyzed cross-coupling reactions of alkylphosphites with vinyl halides (Scheme , a), metal-promoted hydrophosphorylation reactions of terminal alkynes with dialkylphosphites (Scheme , b), and silver-mediated radical phosphonation reaction (Scheme , c) . Metalation of alkynylphosphonates via zirconation or titanation, yielding metallacycle intermediates, followed by hydrolysis of the intermediate, is an efficient route for the stereoselective synthesis of vinylphosphonates (Scheme , d).…”
Section: Introductionmentioning
confidence: 99%
“…The reaction of aryl halides of decreased reactivity may be promoted by Ni salts (at higher temperatures) [44,45]. Vinyl halides may react in the presence of Cu (I) bromide [46].…”
Section: Methodsmentioning
confidence: 99%
“…At the same time, Axelrad (Axelrad et al, 1981a , b ) demonstrated that phosphite- or phosphine- ligated copper(I) chloride complexes could mediate the transformation of alkenyl bromides to the corresponding chlorides, although under harsh conditions and using a stoichiometric amount of the copper complex (Figure 17 , middle).…”
Section: Halogen Exchange In Alkenyl Halidesmentioning
confidence: 99%